The Interpretation of Mu’āsharah bi al-Ma’rūf in the Qur’an and the Enhanced Edition of Tafsir: An Intertextual Analysis by Julia Kristeva - Ikhsan, Mochammad (UIN Sunan Gunung Djati Bandung, 2025)
This article examines how the Ministry of Religious Affairs, through the Al-Qur'an and its Tafsir – Enhanced Edition (AQT-EDS), interprets QS. al-Nisā' verse 19, particularly in emphasizing the principle of mu'āsyarah bi al-ma'rūf as the basis for equality in relations between men and women. This research is qualitative in nature with a literature study method as the data collection technique. The analysis used is Julia Kristeva's intertextuality theory with the QPXT model: Q refers to direct quotations, P to meaning extraction, X to differences in emphasis, and T to meaning transformation. The results show that the P and X patterns are dominant in the interpretation of the Ministry of Religious Affairs. AQT-EDS absorbs many classical meanings regarding the prohibition of 'adl and the restoration of women's rights, but provides a new emphasis on the ethical-procedural dimension by choosing diction that is communicative and popular for the wider community. Thus, this interpretation does not only repeat turāṯ, but also emphasizes the boundaries of behavior that are in line with the values ​​of ma'rūf. This study also noted the absence of a T-pattern, thus the normative direction remains consistent with mainstream interpretations without significant changes in meaning. QS. al-Nisā': 19 in the AQT-EDS is positioned as a normative and ethical basis for the Ministry of Religious Affairs' gender equality policies, including premarital education, gender mainstreaming programs, and anti-violence cultural campaigns in domestic relationships and broader social interactions.